2014
DOI: 10.9790/3008-09528387
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasitic infections and Demographic status of school children in Bhopal region of Central India

Abstract: Background: School going children of age 6-12 years are the prime victims of intestinal parasitic infections. There is scant information available on the prevalence and distribution of intestinal parasites among school children in Bhopal region of Central India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In the present study, only intestinal protozoan parasites were detected. Similarly, other studies reported higher prevalence of protozoan parasites and low prevalence of helminths[ 16 17 ] and suggested the transmission was through contaminated food and water.…”
Section: Discussionmentioning
confidence: 73%
“…In the present study, only intestinal protozoan parasites were detected. Similarly, other studies reported higher prevalence of protozoan parasites and low prevalence of helminths[ 16 17 ] and suggested the transmission was through contaminated food and water.…”
Section: Discussionmentioning
confidence: 73%
“…Cover slip was placed on the emulsion at an angle of 45% to prevent air bubbles from forming under the cover slip. This method was used to detect the presence of motile intestinal parasites, trophozoite and cysts of protozoan parasites under light microscope at 10X and 40X magnification immediately [16]. The remaining part was preserved with 10% formalin in the ratio of 1 g of stool to 3 ml of formalin for later examination at Assosa hospital.…”
Section: Direct Wet Mount Methodsmentioning
confidence: 99%
“…Iodine stain preparation was made from the sediments. Finally, the entire area under the cover slip were systematically examined using ×10 and ×40 objective lenses and ova or cyst of different parasites can be observed under the microscope [16]. Ten percent of the prepared slides were re-checked by an experienced laboratory technologist.…”
Section: Formol-ether Concentrationmentioning
confidence: 99%
“…This can contribute to higher prevalence of parasitic infection. [8,12] It was also noted that 56.11% cases were having drinking water from open well and 10% were using water from borewell. Because these wells are constructed at shallow level, they can come in contact with outer atmosphere and provide optimum condition for survival and development of eggs like A. lumbricoides.…”
Section: Ancylostoma Duodenalementioning
confidence: 99%